PENGARUH WAKTU PEMANASAN TERHADAP KADAR PROKSIMAT, ASAM AMINO SITRULIN DAN SIFAT ORGANOLEPTIKSELAI ALBEDO KULIT SEMANGKA - Mauidzoh, Imroah al; Iswahyudi, Iswahyudi; Putri, Imawati Eka (Jurnal Gizi dan Pangan Soedirman, 2023)
The watermelon rind contained 60% higher citrulline than the watermelon rind albedo. Citrulline has the benefit of lowering blood pressure.This study aimed to determine the effect of heating time of watermelon rind (albedo) on the citrulline amino acids, chemical properties (proximate), and organoleptic properties. This study conducted using a randomized complete block design (RCBD). The treatment wear heating for 35, 40, 45, and 50 minutes. The results showed that heating time had no significant effect on proximate and citrulline levels (p>0.05). The results of the organoleptic test analysis showed that the heating time had a significant effect on liking (<0.05). The results of the analysis of the viscosity test showed that the heating time had a significant effect on the viscosity of the jam (p<0.05). F4 (heating time 50 minutes) is the chosen option with nutritional content per 100 g, namely energy 192.52 Kcal, protein 0.24 g, fat 0.02 g, carbohydrates 47.83 g, water 51.02 g, ash 0 , 08 g, and the amino acid citrulline 96.94 mg.